Prospective association of sex steroid concentrations with periodontal progression and incident tooth loss. (26th January 2016) - Samietz, Stefanie; Holtfreter, Birte; Friedrich, Nele; Mundt, Torsten; Hoffmann, Wolfgang; Völzke, Henry; Nauck, Matthias; Kocher, Thomas; Biffar, Reiner
Abstract: Aim: The aim of this study was to determine the prospective association between sex steroid concentrations with periodontal progression and incident tooth loss in men and women. Methods: We used data from 1465 women and 1838 men (age 20–81 years) with completed five‐year‐follow‐up from the Study‐of‐Health‐in‐Pomerania, a population‐based longitudinal cohort. Serum levels of total testosterone (TT) and other sex steroids were measured. Mean clinical attachment loss (CAL) and the number of teeth were assessed. Generalized regression models were implemented for cross‐sectional and longitudinal analyses, adjusting for age, education, smoking, waist circumference, diabetes, physical activity, blood sampling time and time between baseline and follow‐up. Results: Fully adjusted models revealed no consistent associations between TT and mean CAL, neither in cross‐sectional [men: ß = −0.0004 (−0.023;0.022), p = 0.97; women: ß = −0.033 (−0.057; −0.009), p = 0.006] nor in longitudinal analyses [men: ß = −0.033 (−0.100;0.034), p = 0.33; women: ß = −0.023 (−0.086;0.040), p = 0.47]. For tooth loss, neither cross‐sectional nor longitudinal associations with any of the sex steroid concentrations were found. Conclusions: No consistent associations of sexual steroids with periodontal progression or tooth loss were found. Further cohort studies are necessary to evaluate possible associations between endocrinological parameters, like supra‐ or subphysiologic testosterone concentrations, and periodontal progression or tooth loss.